Transparansi, Hasil Audit Laporan Keuangan dan Korupsi pada Pemerintah Provinsi di Indonesia - Cinintya, Christine; Gamayuni, Rindu Rika; Dharma, Fitra (E-Jurnal Akuntansi; Vol 32 No 9 (2022), 2022)
Transparency and audit results on government management are important things that can be used to reduce corruption. This study aims to determine the effect of transparency, audit findings and follow-up on recommendation of audit results on corruption, using data from 28 provincial governments during 2013 – 2020. The research population is the provincial government in Indonesia, and uses Microsoft Excel and Eviews for data processing. The test results on 224 samples show that transparency has a negative effect on corruption, and audit findings have a positive effect on corruption. Meanwhile, follow-up on recommendation of audit results has no effect on corruption. Keywords: Transparency; Findings; Follow-Up; Corruption